New anticoagulants - Haas, S.; Schellong, S. (Hämostaseologie, 2007)
Heparins and vitamin K antagonists have been the cornerstones of anticoagulation therapy for several decades. Although they are very effective at inhibiting the coagulation process, they have several practical limitations. This was a challenge for the development of therapies that will overcome these drawbacks while matching the efficacy of the two classes of anticoagulants. Advances were achieved in the development of safer, convenient, more specific treatments, which should provide predictable anticoagulant responses and substantially improve the prevention and management of thromboembolic disorders. In the search for new agents matching the ideal anticoagulant profile, different steps in the coagulation cascade have been targeted, including direct thrombin inhibition, and inhibition of factor Xa, factor IXa, the factor Vlla-tissue factor complex and the factor Va-factor Vllla complex. The most advanced clinical development has been achieved with direct factor Xa- and factor IIa-inhibitors which may replace conventional anticoagulants for long-term prevention and treatment of venous and arterial thromboembolic complications.
Keywords: Anticoagulants; factor Xa inhibitors; factor IIa inhibitors; heparins; vitamin K antagonists